AAAI Presidential Panel on Long-Term AI Futures: Interim Report from the Panel Chairs - Horvitz, Eric; Selman, Bart (2009)
The AAAI President has commissioned a study to explore and address potential long-term societal influences of AI research and development. The panel will consider the nature and timing of potential AI successes, and will define and address societal challenges and opportunities in light of these potential successes. On reflecting about the long term, panelists will review expectations and uncertainties about the development of increasingly competent machine intelligences, including the prospect that computational systems will achieve "human-level" abilities along a variety of dimensions, or surpass human intelligence in a variety of ways. The panel will appraise societal and technical issues that would likely come to the fore with the rise of competent machine intelligence. For example, how might AI successes in multiple realms and venues lead to significant or perhaps even disruptive societal changes?
Association for the Advancement of Artificial Intelligence